Hypertension- and glycaemia-lowering effects of a grape-pomace-derived seasoning in high-cardiovascular risk and healthy subjects. Interplay with the gut microbiome. Issue 4 (2nd February 2022) - Taladrid, Diego; de Celis, Miguel; Belda, Ignacio; Bartolomé, Begoña; Moreno-Arribas, M. Victoria
Abstract : Grape pomace (GP) is a winery by-product rich in polyphenols and dietary fibre. Abstract : Purpose : Grape pomace (GP) is a winery by-product rich in polyphenols and dietary fibre. Some recent results suggest that GP-derived extracts could be promising additives in food, specially recommended for low-salt diets. The hypothesis tested in this paper is that the regular consumption of GP-derived seasonings could help in the control of hypertension and glycaemia. Methods : A randomized intervention study (6 weeks) was performed in high-risk cardiovascular subjects ( n = 17) and in healthy subjects ( n = 12) that were randomly allocated into intervention (2 g day −1 of GP seasoning) or control (no seasoning consumed) groups. Blood samples, faeces, urine and blood pressure (BP) were taken at the baseline and at the end of the intervention. Faecal samples were analysed for microbiota composition (16S rRNA gene sequencing) and microbial-derived metabolites (short chain fatty acids and phenolic metabolites). Results : Among the clinical parameters studied, BP and fasting blood glucose significantly decreased ( p < 0.05) after the seasoning intervention, but not for the control group. Notably, application of a novel approach based on ASV (Amplicon Sequence Variant) co-occurrence networks allowed us to identify some bacterial communities whose relative abundances were related with metadata. Conclusion : Our primary findings suggest that GP-seasoning may help in the modulation of cardiometabolic risk factors, mainly in the early stages. Furthermore, it evidences modulation of gut microbiota and functional bacterial communities by grape pomace, which might mediate the cardiometabolic effects of this by-product.